Study of a flexible UAV proprotor. (1st January 2014) - Mohd-Zawawi, Fazila; Lv, Peng; Prothin, Sebastien; Morlier, Joseph; Moschetta, Jean-Marc; Benard, Emmanuel
This paper is concerned with the evaluation of design techniques, both for the propulsive performance and for the structural behaviour of a composite flexible proprotor. A numerical model was developed using a combination of aerodynamic model based on blade element momentum theory (BEMT), and structural model based on anisotropic beam finite element, in order to evaluate the coupled structural and the aerodynamic characteristics of the deformable proprotor blade. The numerical model was then validated by means of static performance measurements and shape reconstruction from laser distance sensor outputs. From the validation results of both aerodynamic and structural model, it can be concluded that the numerical approach developed by the authors is valid as a reliable tool for designing and analysing the UAV-sized proprotor made of composite material. The proposed experiment technique is also capable of providing a predictive and reliable data in blade geometry and performance for rotor modes.